Livestock production in central Mali: Economic characters and productivity indices for Sudanese Fulani cattle in the agro-pastoral system - Wilson, R.T. (1989)
Presents results of a study conducted to analyse the economic characters and productivity indices of Sudanese Fulani cattle in the agro-pastoral system in central Mali. Discusses weight characters including postpartum weight and calf weight, mortality, and productivity indices.